2020
DOI: 10.1107/s2056989020012335
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of melaminium cyanoacetate monohydrate

Abstract: The asymmetric unit of the title compound, 2,4,6-triamino-1,3,5-triazin-1-ium cyanoacetate monohydrate, C3H7N6 +·NCCH2COO−·H2O, consists of a melaminium cation, a cyanoacetate anion and a water molecule, which are connected to each other via N—H...O and O—H...O hydrogen bonds, generating an eight-membered ring. In the crystal, the melaminium cations are connected by two pairs of N—H...N hydrogen bonds, forming tapes along [110]. These tapes develop a three-dimensional network through N—H...O,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The intumescent effect ultimately generates a thermal barrier that protects the underlying substrate from further decomposition. 7 Previous studies have shown the effectiveness of specific acid source additives in intumescent flame-retardant systems including boric acid, 22,23 cyanoacetic acid, 24 phosphoric acid, 25 and sulfuric acid. 25,26 This work compares the FR performance of commonly used acid sources when added to a nonselfextinguishing base recipe consisting of chitosan (CH) and carboxymethyl cellulose (CMC).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intumescent effect ultimately generates a thermal barrier that protects the underlying substrate from further decomposition. 7 Previous studies have shown the effectiveness of specific acid source additives in intumescent flame-retardant systems including boric acid, 22,23 cyanoacetic acid, 24 phosphoric acid, 25 and sulfuric acid. 25,26 This work compares the FR performance of commonly used acid sources when added to a nonselfextinguishing base recipe consisting of chitosan (CH) and carboxymethyl cellulose (CMC).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Previous studies have shown the effectiveness of specific acid source additives in intumescent flame-retardant systems including boric acid, , cyanoacetic acid, phosphoric acid, and sulfuric acid. , This work compares the FR performance of commonly used acid sources when added to a nonself-extinguishing base recipe consisting of chitosan (CH) and carboxymethyl cellulose (CMC). CH ,, and CMC , have been shown to be effective bio-sourced components in fire-retardant films.…”
Section: Introductionmentioning
confidence: 99%